2010
DOI: 10.1177/147323001003800402
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions concerning Pain Management in the Treatment of Rheumatoid Arthritis

Abstract: Previous qualitative studies have revealed discrepancies between patients' and physicians' perceptions of rheumatoid arthritis (RA) and its treatment. Questionnaires were administered to 2795 patients with RA (756 from Europe; 2039 from the USA) to measure patients' perceptions regarding pain management in RA. Although the majority of patients reported their RA as somewhat-to-completely controlled, 75% of European and 82% of US patients reported their pain as moderate-to-severe in the previous 2 months. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(130 citation statements)
references
References 21 publications
5
119
2
4
Order By: Relevance
“…In this respect, our data confirm and extend previous data from Taylor et al 3, who reported in 2010 that a majority of the RA patients studied in Europe (60%) and the US (65%) reported discontent with pain management. That study notably included both established and early RA, whereas our patient cohort consisted only of early RA patients included at diagnosis and who thereafter received their first DMARD treatment with MTX.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this respect, our data confirm and extend previous data from Taylor et al 3, who reported in 2010 that a majority of the RA patients studied in Europe (60%) and the US (65%) reported discontent with pain management. That study notably included both established and early RA, whereas our patient cohort consisted only of early RA patients included at diagnosis and who thereafter received their first DMARD treatment with MTX.…”
Section: Discussionsupporting
confidence: 92%
“…In spite of effective immune‐suppressive therapies, observational studies show that a large number of patients continue to have significant pain, which is known to affect both quality of life and work capacity 2. In an international observational study of patient‐reported outcomes, the majority of the cohorts with established RA in Europe (60%) and the US (65%) reported discontent with pain management 3. In early arthritis, active joint inflammation causes a significant burden of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Pain is a significant problem for many patients with inflammatory polyarthritis (IP) and rheumatoid arthritis (RA) (1). Most often it is pain that initially motivates them to seek medical care (2).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a number of published studies examining patients' preferences for drug treatments in rheumatoid arthritis (RA) (21)(22)(23)(24)(25)(26)(27)(28)(29), few have looked at parents' preferences for drug treatments in JIA. Barron et al (30) focused on parents' preferences for nonsteroidal antiinflammatory drug (NSAID) treatments in JIA, using contingent valuation to examine parents' willingness to pay for a drug that leads to remission over one that eliminates gastrointestinalrelated side effects.…”
Section: Introductionmentioning
confidence: 99%